APPLICATION OF ISLAMIC BUSINESS ETHICS IN RUNNING MICRO SMALL AND MEDIUM MSME ENTERPRISES - Putri, Naila; Fany, Nicole Theo; Basyir, Muhammad Fiqry; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine the application of Islamic business ethics in running Micro, Small and Medium businesses in the Umi Zahra Clothing Store industry. The research approach used is a qualitative approach. The research method involves interviews with owners and employees of Micro, Macro and Medium Enterprises. Based on the results of implementing Islamic business ethics in running a business at the Umi Zahra Clothing Store, it starts with always prioritizing honesty, trustworthiness, prioritizing the quality of the product itself, strengthening customer relationships and making a positive contribution to the growth of UMKM and integrating the values of Islamic Ethics.